Analisis Aspek Perkembangan Remaja terhadap Prokrastinasi Akademik Siswa di SMAN 92 Jakarta - Aprilia, Sekar; Lestari, Melina (Universitas Muhammadiyah Metro, 2024)
Academic procrastination is a common issue among teenagers and students and can have negative effects on their academic performance and mental health. At the same time, adolescent development involves significant physical, emotional, and social changes that can impact how students manage their time and academic responsibilities. Therefore, it is important to understand how specific aspects of adolescent development contribute to academic procrastination. This research uses a qualitative approach with a narrative method. The participants in this study are students from SMAN 92 Jakarta. The aim of this research is to determine whether aspects of adolescent development influence academic procrastination. The study uses interview guidelines as a tool for data collection. After gathering data from the field, the researcher will analyze it using an interactive model by Miles & Huberman, involving data reduction, data presentation, and drawing conclusions/verification. The results of this study indicate that respondents’ perspectives on delaying the start of tasks include (1) lack of understanding of the task; (2) intention to complete the task; and (3) underestimating the task. Students often fulfill their obligations as learners by completing assignments, earning grades, or honing their skills when given daily tasks. Enjoyable activities for students include engaging in non-learning-related activities and preferring to study or work on tasks in groups.